[PP.37.12] INFLUENCE OF WAVE REFLECTION AND VASCULAR STIFFNESS PARAMETERS ON CARDIAC STRUCTURE AND FUNCTION IN PATIENTS AT RISK OR WITH TYPE 2 DIABETES. (September 2016) - Faconti, L.; Mills, C.E.; Govoni, V.; Casagrande, M.L.; Yao, L.; Webb, A.; Cruickshank, J.K.
Abstract : Objective: Left ventricular (LV) diastolic dysfunction, LV hypertrophy and increased arterial stiffness are common in type 2 diabetes (T2DM); however, the relation between these pathophysiological factors remains unclear. We investigated the relationship between arterial function and cardiac structure and function, in people at risk of or with T2DM. Design and method: 83 patients (47% non-European) participated in the study. Cardiac indices, arterial elastance (EA) and ventricular elastance (ELV) were estimated by conventional 2-dimensional echocardiography. Aortic pulse wave velocity (PWV) and augmentation index (AIx) were measured with an Arteriograph, cardio-ankle vascular index (CAVI), nominally independent of blood pressure (BP), by a VaSera device. Results: Mean age was 57y, 75% had T2DM, 84% hypertension, 12 % previous cardiovascular events; 89% of the population had normal LV filling pressure (E/e' = 7.7 ± 2.3) and mean LV mass index (LVMI) was 52.5 g/m2.7. PWV (9.4 ± 1.7 m/s) and AIx (27.9 ± 15.8 %) were both related with BP (p < 0.05) while CAVI (8.3 ± 1.2) was not. Tissue Doppler indices (TDI) of diastolic function (E' septal and lateral waves) were inversely related with AIx (β=-0.27 and -0.37) as they were with CAVI (β=-0.14 and -0.25) and PWV (β=-0.29 and -0.23) (all p < 0.05); instead only regressions for AIx with LVMI and left atrium volume index (LAVI) were significant (β=0.28 and 0.42, p < 0.001). In multiple regression models adjusted for BP, age, gender and BMI, AIx was still significantly associated with cardiac structure: LVMI and LAVI (all p < 0.05), and CAVI with diastolic function (E' septal), also independently of LVMI (p < 0.05). PWV was not related to these indices. Moreover only AIx and arterial elastance (an integrated index of arterial vascular load), were related with ELV (an index of myocardial contractility and systolic stiffness) after adjusting for age, gender, BP and LVMI (p < 0.05). Conclusions: In a multi ethnic cohort of patients at risk of or with T2DM, pressure augmentation was related to cardiac remodelling and myocardial systolic stiffness while a generally pressure-independent index of stiffness of the aorta, femoral and tibial artery (CAVI) was associated with TDI of diastolic function.